Formulation and optimization of etravirine loaded polymeric nanoparticles by applying doe approach - NILA MARY VARGHESE, (International Journal of Pharma and Bio Sciences, 2019)
The aim of the study was to formulate and optimize Etravirine (ETR) loaded Poly (lactic-co-glycolic acid) (PLGA) nanoparticles using Design of Experiment (DoE) approach to obtain the final product with the desired quality profile. The nanoparticles were prepared by single emulsion solvent evaporation technique and optimization of the formulation variables were done by employing 32 full factorial design of DoE approach. The nanoparticles were characterized for particle size, zeta potential, entrapment efficiency, and in vitro drug release kinetics. The nanoparticles were formulated and optimized. The optimized batch of ETR-PLGA nanoparticles exhibited a particle size of 127.9nm, have zeta potential of -5.94mV and entrapment efficiency of 79.18%. The Differential scanning calorimetric (DSC) studies of the formulation indicated the entrapment of the drug in the polymeric matrix and the drug exhibited a change in crystalline form to amorphous in the formulation. The in vitro release of the drug from the formulation was found to 70.54±1.86% following non-fickian Higuchi model kinetics. The results from the study revealed the applicability of 32 full factorial design in identifying the critical formulation parameters for the preparation of the optimized ETR loaded PLGA nanoparticles.